If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14x+3=6x-9
We move all terms to the left:
14x+3-(6x-9)=0
We get rid of parentheses
14x-6x+9+3=0
We add all the numbers together, and all the variables
8x+12=0
We move all terms containing x to the left, all other terms to the right
8x=-12
x=-12/8
x=-1+1/2
| 10=n/6-3 | | 3k-10k+5=5k+17 | | 12x=12x+19 | | -10f+3=-1-10f+2 | | 78-g=24 | | 19=18+y3 | | –3+5n=4n | | 2a(2a+a)=360 | | 3.3=1.2-0.4y | | 4^2x+1=8^x-1 | | 8q+3q-9q-q+3q=4 | | 3x–7=3(x+1) | | 5n=6=-3n-10 | | -1+7x=4+11x | | 8/7n-3=5 | | 5+b=1+2b | | 6=5+u2 | | 5(b+4)=20 | | 8.6x+22(2x-5)=54 | | 20=–10(t+8) | | 37x=85 | | -4(2x+9)=-8x-36 | | 6-4(2x+1)=2-(15-3x)-x | | 0.985X(x+7,11)=15 | | -5(2x+6)=8 | | 3=–z–75 | | 4/7w=13/1/7 | | 9x=1525 | | 6+v5=7 | | 6x^2-11x-32=0 | | 7(p-3)+9=5(p-2)-3p | | 4b−7=1+5b |